Variation of roasting temperature in making cookies with barlin banana flour base and skin (Musa Acuminata AA) on dietary fiber content and organoleptic test (Fakultas Teknik, Universitas Negeri Semarang, 2018)
The purpose of this study was to use barlin banana peel waste (Musa acuminata AA) with flour made together as well as the banana fruit. Barlin banana flour with skin is made into a cake. The results of these cookies are tested in the laboratory to determine the content of dietary fiber. This type of research is experimental research. The production starts from fresh barlin banana into berlin banana flour. The process of making cookies using a roasting process at a different temperature of 170oC, 175oC, and 180oC for 10 minutes. Test the nutritional content of barlin banana flour mixed with the skin containing 3.96 dietary fiber. The content of dietary fiber in cakes is made from barlin banana flour mixed with the roasting process, the higher the heating temperature, the less the fiber content of the food reaches 3.89%. In the organoleptic test, cakes tested on 20 respondents resulted in 60% agree, for the texture of crispy cookies in 25% approve and 75% strongly agreed, for the Â aroma of fragrant cakes, stating 40% agreed, and 45% strongly agreed, to the taste of cookies that are crisp 40% approved and 50% strongly agreed.